Theoretical and Numerical Analyses of an Aluminium-Concrete Composite Beam with Channel Shear Connectors - POLUS, Łukasz; SZUMIGAŁA, Maciej (Engineering Transactions, 2019)
This paper presents a numerical simulation and a theoretical investigation of an aluminiumconcrete composite (ACC) beam subjected to bending. ACC structures are similar to steel-concrete composite (SCC) structures. However, their girders are made of aluminium instead of steel. The use of ACC structures is limited because of the lack of relevant design rules. Due to this fact the authors suggest applying the theory for SCC structures to ACC structures. In this paper, the methods for calculating the bending resistance and the stiffness of ACC beams were presented. What is more, the results from the theoretical investigation were compared with the results from the laboratory tests conducted by Stonehewer in 1962. The calculated plastic resistance moment of the ACC beam with partial shear connection was 1.2 times lower than the bending resistance from the laboratory test. The calculated stiffness was 1.1 higher than the stiffness from the laboratory test. What is more, the authors of this paper prepared two numerical models of the ACC beam. The analysed models had different types of connection between the aluminium beam and the concrete slab. In the first variant, the aluminium beam was permanently connected with the concrete slab to model full composite action. In the second variant, the aluminium beam and the concrete slab were connected using zero-length wires, the characteristics of which were taken from the laboratory test, to take slip into account. The numerical model with zero-length springs adequately captured the elastic response of the ACC beam from the laboratory test conducted by Stonehewer.